"I did not know there was another life": Meanings of life in the out‐of‐home Mothers Unit reunification programme. Issue 3 (7th December 2017) - Tener, Dafna; Sorek, Yoa; Schwartz, Ella
Abstract: The Mothers Unit is a reunification and treatment programme in a welfare emergency centre in Israel. The unit is the only one in Israel offering joint residence for mothers at risk of abusing or neglecting their children. The unit provides an alternative to out‐of‐home care for young children suffering from maltreatment in order to enable them and their mothers to return to the community together at the end of the treatment. The current qualitative study examines the lived experiences of the women and their children from the subjective perspective of the women currently or previously involved in the programme and of the professionals working with them. Thematic analysis of 36 in‐person semi‐structured interviews reveals the multiple meanings they attribute to life in the Mothers Unit and its perceived effects on their children and themselves.